Improving communication partner training of familiar partners of people with aphasia: results of a pilot stepped wedge implementation trial and embedded process evaluation - Shrubsole, Kirstine; Rogers, Kris; Wallace, Sarah J.; Isaacs, Megan; Ong, Wen Xuan; Worrall, Linda; McCluskey, Annie; Power, Emma (Disability and rehabilitation, 2025)
Communication Partner Training (CPT) improves communication between people with aphasia and their families and friends, but there is considerable variation in practice. We evaluated the outcomes of an implementation package on speech pathologists' delivery of CPT to familiar partners of people with aphasia, and factors influencing outcomes. 12-month pilot stepped wedge cluster non-randomised controlled trial and process evaluation involving three health services. Implementation package included online training, workshops, resources, and support. Data were collected through audits, clinician behaviour-change surveys, training logs, checklists, questionnaires, and focus groups. Thirty-six clinicians participated, and 113 patient files were audited. Post-implementation, there was a 26% increase in familiar partners being offered CPT and an 18% increase in those provided CPT. Significant improvements were recorded between immediate pre/post implementation time-points (offering CPT: = 0.004; providing CPT: = 0.021), and more comprehensive CPT practice was provided, but change was not sustained. Total behaviour-change scores increased ( < 0.001), with a higher intervention effect for targeted domains ( < 0.001). Clinicians reported valuing and intending to implement CPT, but organisational barriers and patient-partner dynamics impacted outcomes. Short-term improvements in CPT practice were observed, but change was not sustained. Longer-term support and CPT tailored to readiness and stage of recovery is needed.